PERILAKU ORANG TUA SISWA SEKOLAH DASAR NEGERI SAWAH PANGGANG GUNUNGKIDUL DALAM MEMBERIKAN MAKANAN BERSERAT - Eka Putranti Meiliana Sari (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2017)
This study aimed to describe parents’ behavior in giving fiber foods. Type of this study was a descrtiptive research. Research object was behavior in concuming fiber foods, the research subject was the students of SD Negeri Sawah Girisekar Panggang Gunungkidul, and the source data was students’ parents of SD Negeri Sawah Girisekar Panggang Gunungkidul. Data collection methods used questionaires. Data analysis technique used a descriptive and quantitative analysis to descrube the category of the variable. This study shows that the parents’ behavior in giving fiber foods of the students of SD Negeri Sawah Girisekar Panggang Gunungkidul was in enough category with the relative frequency 45.59%. It means that students’ parents were good enough in giving fiber foods. From the indicators concisted of knowledge, attitude, and action show also in enough category. Indicator of knowledge in concuming fiber foods was in enough category with the relative frequency 55.88%. The indicator of attitude in concuming fiber foods was in enough category with the relative frequency 38.24%. Indicator of action in concuming fiber foods was in enough category with the relative frequency 61.76%. Key words: parents’ behavior, of giving fiber foods